2014
DOI: 10.1007/s10886-014-0434-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Cyanogenic Glycosides Across Populations of Wild Lima Beans (Phaseolus lunatus) Has No Apparent Effect on Bruchid Beetle Performance

Abstract: Cyanogenic glycosides (CNGs) act as feeding or oviposition deterrents and are toxic after enzymatic hydrolysis, thus negatively affecting herbivore performance. While most studies on CNGs focus on leaf herbivores, here we examined seeds from natural populations of Phaseolus lunatus in Mexico. The predominant CNGs, linamarin and lotaustralin, were quantified for each population by using ultra-high pressure liquid chromatography-mass spectrometry. We also examined whether there was a correlation between the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…Under this scenario, parasitoid fitness would not be expected to vary between plant species, as observed in this study. In support of this interpretation, previous work has shown that Z. subfasciatus can tolerate high concentrations of cyanogenic compounds present in P. lunatus (lima bean) without exhibiting detectable reductions in fitness correlates (Shlichta et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Under this scenario, parasitoid fitness would not be expected to vary between plant species, as observed in this study. In support of this interpretation, previous work has shown that Z. subfasciatus can tolerate high concentrations of cyanogenic compounds present in P. lunatus (lima bean) without exhibiting detectable reductions in fitness correlates (Shlichta et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Toxic compounds are also present in some legumes. Lima beans ( Pheaseolus lunatus ), together with many other legumes, contain cyanogenic glucosides, which cause respiratory distress when consumed in high quantities (Shlichta, Glauser, & Benrey, ). In the grass pea Lathyrus sativus , a nonprotein amino acid, β‐N‐oxalyl‐l‐α,β‐diaminopropionic acid (β‐ODAP), is present.…”
Section: The Benefit Of Legumesmentioning
confidence: 99%
“…For the experiments we used seeds from three cultivated varieties and three wild populations of P. lunatus (Figure 1) Shlichta et al, 2014). We collected seeds from 10 plants per site (only six for HGO).…”
Section: Seedsmentioning
confidence: 99%